Blend de óleos essenciais em dietas com fonte de fibra não volumosa para novilhos nelore confinados - Fonseca, Alessandra Schaphauser Rosseto (2022)
The aim of this study was to assess the effects of a blend of essential oil, based on cinnamaldehyde and diallyl disulfite, associated or not antibiotics on nutritional and metabolic parameters for feedlot Nellore steers fed non-forage based diet. Five Nellore cattle (252.6 ± 29.8 kg of body weight), steers, with 14 months old, cannulated in the rumen were distributed in 5x5 Latin Square design simple. The treatments assessed were a basal noroughage diet with inclusion of sodic monensin (MON), sodic monensin + virginiamycin (MV), sodic monensin + blend of OE (MOE25), sodic monensin + blend of OE (MOE35) and blend of essential oil (OE). Feed, orts, feces, ruminal fluid, blood and urine samples were utilized for assess the intake, digestibility, ruminal pH, ruminal NH3, nitrogen balance, microbial nitrogen synthesis, fecal cortisol metabolites, blood glucose and D and L-lactate. No difference (P>0.05) of additives in intake, nutrients digestibility and ingestivo behavior. There tendency (P=0,0553) of effect of additives for ruminal pH, the MV presented the highest value. No difference (P>0.05) between additives and duration for which pH was below 5.8; 5.5 and 5.2 and the same occurred for the ruminal NH3, microbial N synthesis and nitrogen balance concentration. The blood glucose and the D e L-lactate concentration was not affected (P>0.05) by additives. No difference (P>0.05) between additives for fecal cortisol metabolites concentration. The blend of essential oils based for cinnamaldehyde and diallyl dissufite is indicated in replacement or association with antibiotic in non-forage based diet for Nellore steers.